Removal of nitric oxide (no) using high energy electron beam and dielectric barrier discharge / Siti A'iasah Binti Hashim - Hashim, Siti A'iasah (2015)

(untitled)
Nitric oxide is a gaseous air pollutant which is a precursor to nitrogen oxides and in the atmosphere it reacts chemically with gaseous hydrocarbons to form other photochemical contaminants such as ozone (O3), peroxyacetal nitrate (PAN) and other photochemical oxidants. Non thermal plasma methods namely, electron beam and dielectric barrier discharge have been studied as promising methods to control NO/ NOx. Basically both methods run as plasma oxidation process where excited electrons produce radicals that will oxidize the targeted pollutants. Investigations using the electron beam flue gas treatment indicate that processing temperature, moisture content, beam current and radiation dose are the important parameters in determining the removal efficiency of nitric oxides. Removal efficiency of 90% was obtained by providing absorbed dose of 14 kGy, and by keeping the humidity of the flue gases at the inlet, to about 13% v/v and temperature around 70 °C. Experiments using the DBD reactor were carried out at room temperature using different mixtures of gases. With the right combination of flow rate, discharge voltage, number of DBD cells and connecting configuration, the reactor can remove up to 80% nitric oxide in the reduction mode. Side by side, the two methods have potentials for applications depending on the processing flow rate, safety and technical requirements.